2009
DOI: 10.1073/pnas.0912920107
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 imposes a type II EBV gene expression on type III and type I B cells by the repression of C- and activation of LMP-1-promoter

Abstract: Epstein-Barr virus (EBV) is associated with a variety of human tumors. Although the EBV-infected normal B cells in vitro and the EBV-carrying B cell lymphomas in immunodeficient patients express the full set of latent proteins (type III latency), the majority of EBVassociated malignancies express the restricted type I (EBNA-1 only) or type II (EBNA-1 and LMPs) viral program. The mechanisms responsible for these different latent viral gene expression patterns are only partially known. IL-21 is a potent B cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 51 publications
2
79
0
Order By: Relevance
“…LMP1 is induced by CD4 ϩ T cell-derived cytokines like IL-4, IL-10, IL-13, and IL-21 (18)(19)(20), which is probably the mechanism through which the T cells provide help for the in vitro growth of the infected B cells. IL-6 is another cytokine known to be a growth factor for EBV-infected B cells (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMP1 is induced by CD4 ϩ T cell-derived cytokines like IL-4, IL-10, IL-13, and IL-21 (18)(19)(20), which is probably the mechanism through which the T cells provide help for the in vitro growth of the infected B cells. IL-6 is another cytokine known to be a growth factor for EBV-infected B cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…For survival and proliferation of the EBV-carrying type IIa cells, inter-actions with the microenvironment are required (17). Results from our laboratory have shown that a number of cytokines (interleukin-4 [IL-4], IL-13, and IL-21) contribute to the induction of expression of LMP1 (18)(19)(20) and probably help the survival and proliferation of latency IIa cells in vivo.…”
mentioning
confidence: 99%
“…LMP-1 plays a central role in EBV biology, since it acts in part as a constitutively active CD40 receptor analog and is essential for B cell proliferation and transformation by EBV (24). In type III latency, EBNA-2 is the major transactivator of the LMP promoters, while in type II latency, depending on the cellular context, different cytokines , are responsible for the activation of LMP-1 transcription (20,26,27,28).Type I interferons (IFNs) are produced in relatively large amounts in response to pathogen sensing by the innate immune system (46). In addition to their direct antiviral activities, these proteins also have antiproliferative and immunomodulatory properties.…”
mentioning
confidence: 99%
“…mal amounts of LMPs [1,4,22,23]), the type I BL lines Akata (45), Rael (32), and Jijoye-M13 (27), the type III BL line Raji (28), and the cord blood-derived LCL CBM1-Ral-STO, transformed with the Rael EBV strain (7). IFN-␣ treatment for 24 h led to the upregulation of LMP-1 protein expression in Jijoye-M13 cells and in all the BL lines carrying EBNA-2-deleted virus, while LMP-1 mRNA and protein levels did not increase in the other cell lines ( To analyze the kinetics and specificity of LMP-1 upregulation, LMP-1 mRNA and protein levels were measured together with LMP-2A and ISG56 mRNA expression in Daudi cells treated with IFN-␣ for 1, 3, 6, and 24 h (Fig.…”
mentioning
confidence: 99%
“…In EBV-associated lymphomas, latencies type I or II, both with a limited expression of EBV proteins, predominate. Kis et al [7] demonstrate that in type I latency, IL21 activates STAT 3, with expression of LMP1 but not EBNA2 and downregulation of proliferation. In type III latency, LMP-1 was upregulated as well, but LMP-2a was repressed.…”
Section: B-cell Lymphomasmentioning
confidence: 99%